Respostas
respondido por:
2
4+x(x-4)=x
4+x²-4x=x
4+x²-4x-x=0
x²-5x+4=0
a=1 b=-5 c=4
Δ=b²-4.a.c
Δ=-5²-4.1.4
Δ=25-16
Δ=9
x'=-b+√Δ/2.a
x'=-(-5)+√9/2.1
x'=+5+3/2
x'=8/2
x'=4
x''=-b-√Δ/2.a
x''=-(-5)-√9/2.1
x''=25-3/2
x''=22/2
x''=11
4+x²-4x=x
4+x²-4x-x=0
x²-5x+4=0
a=1 b=-5 c=4
Δ=b²-4.a.c
Δ=-5²-4.1.4
Δ=25-16
Δ=9
x'=-b+√Δ/2.a
x'=-(-5)+√9/2.1
x'=+5+3/2
x'=8/2
x'=4
x''=-b-√Δ/2.a
x''=-(-5)-√9/2.1
x''=25-3/2
x''=22/2
x''=11
respondido por:
1
4 + x (x - 4) = x
4 + x² - 4x = x
4 + x² - 4x - x = 0
x ²- 5x + 4 = 0
4 + x² - 4x = x
4 + x² - 4x - x = 0
x ²- 5x + 4 = 0
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás